Periodontitis and Its Role in Oral Cancer Susceptibility: A Case-Control Study - Reddy, Sujatha S.; N., Rakesh; Prashanth, Radha; Choudhary, Ruchika; S., Sruthy (Indian Journal of Medical and Paediatric Oncology, 2024)
Introduction Oral cancer and periodontitis are complex, multifactorial diseases, influenced by common risk factors such as genetic predisposition, lifestyle choices, and oral health practices. While certain studies indicate a positive correlation between periodontitis and oral cancer, the precise mechanisms and causation remain unclear.Objective This study aims to determine if individuals with periodontitis have a heightened risk of developing oral cancer compared with those with healthy periodontal conditions.Materials and Methods One hundred and twenty-six participants, 63 with oral cancer and 63 without oral cancer, were enrolled. A structured questionnaire was developed to gather data on demographics, socioeconomic status, lifestyle risk factors, dietary habits, periodontal condition, oral hygiene practices, and complete oral health status. Statistical analysis used chi-squared and Mann–Whitney U tests and logistic regression to understand potential influences on oral cancer development.Results Notable associations were identified between oral cancer occurrence and specific socioeconomic factors and lifestyle behaviors, including gender, age, education level, and tobacco and alcohol usage. Average Silness and Loe plaque index values, probing pocket depth, and clinical attachment loss values were significantly higher in cases than controls. Patients with periodontitis exhibited a higher incidence of oral cancer (63.9%) compared with those without periodontitis (32.4%).A substantial majority of oral cancer patients (72.9%) exhibited stage 4 periodontitis, contrasting with controls (30.6%).Conclusion Periodontitis emerges as a significant individual risk factor influencing oral cancer development. Rigorous monitoring is recommended for individuals with compromised periodontal health, particularly with severe periodontitis and concurrent risk factors. Prioritizing preservation of periodontal health in high-risk individuals holds promise for mitigating oral cancer–associated risks.
Keywords: periodontitis; oral cancer; risk factors; chronic inflammation; tobacco